Why the Mediterranean diet? - Chudzińska, Małgorzata; Nartowicz, Małgorzata; Zukow, Walery; Sinkiewicz, Władysław (Journal of Education, Health and Sport, 2018)
"Mediterranean diet" is a concept that defines a certain range of nutritional behaviors that cannot be faithfully reproduced in current times. The prototype of this diet was created in Crete in the 1960s and spread mainly among poor populations of fishermen and shepherds, leading a lifestyle substantially differed from modern one. The Mediterranean diet is characterized by high consumption of vegetables and fruit, cereal products, legume seeds and olive oil, average consumption of fish, dairy products and alcohol, as well as small consumption of meat, sugar and confectionery products. The products recommended in it contain a number of pro-health properties, among others, thanks to the content of omega-3 fatty acids, monounsaturated fatty acids, fiber, and antioxidants. Therefore, the Mediterranean diet allows to develop good eating habits for life and prevents many civilization diseases.